Reparative Confiscation in the ECtHR Case Law: Pragmatic Lessons from Florio and Bassignana v. Italy for the Ukrainian Legal System : Preprint - Туляков, Вячеслав Олексійович; Туляков, В. О.; Tuliakov, Viacheslav O. (Elsevier, 2026)
This article examines the European Court of Human Rights' landmark judgment in Florio and Bassignana v. Italy, which establishes critical boundaries between reparative and punitive functions of confiscation under Article 1 of Protocol No. 1 to the European Convention on Human Rights. The Court held that mechanical combination of confiscation already performing a restorative function with full civil or audit compensation, without considering the cumulative effect, transforms a reparative instrument into an excessive burden constituting a double sanction incompatible with proportionality requirements. The analysis explores implications of this judgment for the Ukrainian legal system, particularly regarding special confiscation under the Criminal Code, sanctions-based confiscation mechanisms, and their interplay with civil compensation claims in corruption cases, crimes against national security foundations, and war crimes. The article argues that Ukraine must adopt crediting mechanisms ensuring that confiscated amounts are counted toward reparative claims of the same beneficiary, implement clear judicial reasoning distinguishing reparative from punitive sums, and demonstrate proportionality in the cumulative package of interferences. The study concludes that confiscation with reparative function already constitutes partial compensation, and state recovery of the same money again represents not restoration but disguised punishment, creating significant risks of violations under the Convention standards. У цій статті розглядається знакове рішення Європейського суду з прав людини у справі Флоріо та Бассіньяна проти Італії, яке встановлює критичні межі між репаративною та каральною функціями конфіскації згідно зі статтею 1 Протоколу № 1 до Європейської конвенції з прав людини. Суд постановив, що механічне поєднання конфіскації, яка вже виконує відновлювальну функцію, з повною цивільною або аудиторською компенсацією, без урахування кумулятивного ефекту, перетворює репаративний інструмент на надмірний тягар, що становить подвійну санкцію, несумісну з вимогами пропорційності. В аналізі досліджуються наслідки цього рішення для правової системи України, зокрема щодо спеціальної конфіскації згідно з Кримінальним кодексом, механізмів конфіскації на основі санкцій та їхньої взаємодії з цивільними позовами про компенсацію у справах про корупцію, злочини проти основ національної безпеки та воєнні злочини. У статті стверджується, що Україна повинна запровадити механізми зарахування, що забезпечують врахування конфіскованих сум до репаративних позовів того самого бенефіціара, запровадити чітке судове обґрунтування, що розрізняє репаративні та штрафні суми, та продемонструвати пропорційність у кумулятивному пакеті втручань. У дослідженні зроблено висновок, що конфіскація з репаративною функцією вже є частковою компенсацією, а державне стягнення тих самих коштів знову ж таки є не відновленням, а замаскованим покаранням, створюючи значні ризики порушень згідно зі стандартами Конвенції.
Tuliakov V. O. Reparative Confiscation in the ECtHR Case Law: Pragmatic Lessons from Florio and Bassignana v. Italy for the Ukrainian Legal System / V. O. Tuliakov. - February 05, 2026. - 8 р. - (Preprint). - Режим доступу: Available at SSRN: https://papers.ssrn.com/sol3/papers.cfm?abstract_id=6181360 ; Publication date : 05 Feb., 2026 ; https://hdl.handle.net/11300/31958
Keywords: reparative confiscation; punitive confiscation; special confiscation; ECtHR; Florio and Bassignana v. Italy; Article 1 Protocol No. 1; proportionality test; cumulative effect; double recovery; crediting mechanism; Ukrainian criminal law; sanctions-based confiscation; war crimes reparations; anti-corruption measures; excessive burden.; репаративна конфіскація; каральна конфіскація; спеціальна конфіскація; ЄСПЛ; Флоріо та Бассіньяна проти Італії; стаття 1 Протоколу № 1; тест на пропорційність; кумулятивний ефект; подвійне стягнення; механізм зарахування; кримінальне право України; конфіскація на основі санкцій; відшкодування за воєнні злочини; антикорупційні заходи; надмірне навантаження